How to explain errors in budget balance forecasts in euro area countries? Empirical evidence based on real-time data - Maritta Paloviita; Pasi Ikonen (Bank of Finland, 2016)
The aim of this study is to explore budget planning in the euro area countries in 2004-2014. Our analyses are based on annual real-time data from the IMF World Economic Outlook publications. As forecasts made by different institutions are strongly correlated, our dataset reasonably reflects information available for policy makers in real-time. We examine whether real-time forecasts of overall budget balance, real GDP growth and output gap have been systematically biased. We also analyse forecast accuracy of potential output growth, which we construct using different vintages of real-time data. Our results indicate systematic biases in forecasts. Further, we study how real-time macroeconomic conditions affect budget planning. For comparison, we also consider how ex post economic conditions and ex post budget balance developments are related. We find robust evidence of mean reversion in budget balances, in both real-time and revised data. Mean reversion is related only to negative budget balances, and it is systematically stronger with respect to revised information. Finally, we analyse errors in budget balance forecasts. We provide robust evidence that revisions to current budget balance have contributed to errors in budget balance forecasts. We also find that forecasted macroeconomic conditions (potential output growth and real GDP growth) and their revisions have affected errors in budget balance forecasts. Overall, our results indicate that real-time uncertainty and revisions materially affect budget planning.
URN:NBN:fi:bof-201606201216
Keywords: E62; E32; 330